MIGRATION OF LEAD IN NON-METAMICT ZIRCON - Bogomolov Y.S. (My University, 1991)
The problem of activation energy calculations of lead loss from zircon and the determination of the lead diffusion coefficient in zircon based on the kinetics of diffusion is dealt with. The experimental technique for the evaluation of the diffusion parameters used in this study is thermal ionization mass-spectrometry (ThIMS). The results of experiments on the kinetics of lead loss from several zircons under linear heating, step heating and isothermal heating regimes are considered. The study of effects of grain size on the kinetics of lead loss is performed under all regimes. A comparison of various mechanisms of lead diffusion in zircon is also made. The experimental results may be much better explained by the principles of volume diffusion than by those of first-order reactions. The values of activation energies calculated from volume diffusion are in the range 7.8 to 9.5 eV for crystalline zircons. The suitability of ThIMS technique for lead migration studies is considered.